(untitled) (Research, Society and Development, 2022)
Melatonin (N-acetyl-5-methoxytryptamine) is a hormone that acts on plant growth, development, and stress response, boosts antioxidant enzymes, non-enzymatic antioxidants, and enzymes related to the repair of oxidized proteins. His study still has many gaps to be explored and answered. The exogenous supply coordinates other signaling molecules to regulate ripening, senescence, spoilage, and postharvest injury of fruits through crosstalk with auxin, abscisic acid, ethylene, gamma-aminobutyric acid, jasmonic acid, nitric oxide, reactive oxygen species, and acid. salicylic. Vegetable oils extracted from fruits are excellent sources of bioactive compounds that are important for maintaining health, but which can deteriorate during storage. Melatonin induces the accumulation of fatty acids helping to preserve these nutraceutical properties for a longer period of time. The methodology used to prepare this review consisted of systematic bibliographic research with the identification of information regarding the influence of melatonin on the properties of the fruits post-harvest. The research aimed to investigate the influence of exogenous melatonin in maintaining the lipid properties of fruits after harvest. A better understanding of the molecular, biochemical, and physiological activities of melatonin helps to develop post-harvest management technologies. It is concluded that the lipid layer of fruit cells is preserved for a longer period of time by the exogenous supply of melatonin.